2020
DOI: 10.1002/jmv.26064
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhetinic acid and its derivatives as potential alternative medicine to relieve symptoms in nonhospitalized COVID‐19 patients

Abstract: SARS‐CoV‐2 is highly infectious, and infection by this virus results in COVID‐19, manifesting predominantly symptoms in the lower respiratory system. Detection of viral genomic materials by RT‐PCR is the gold standard for diagnosis. Suspected COVID‐19 patients who had a documented history of exposure and exhibited symptoms, but did not have positive PCR test results, were generally self‐quarantined with prescriptions aiming to help attenuate their symptoms. These prescriptions are however neither specific nor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…Treatment with GA can also alleviate β-amyloid ( Ahn et al, 2006 ; Zhao et al, 2013 ) or systemic LPS-induced ( Song et al, 2013 ) cognitive impairment via inhibition of neuroinflammation. Some COVID-19 patients have been alleviated symptoms using diammonium glycyrrhizinate, an ammonium salt preparation of 18-alpha-GA ( Ding et al, 2020 ; Li et al, 2020 ). This phenomenon could be explained by the anti-inflammatory properties of GA.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with GA can also alleviate β-amyloid ( Ahn et al, 2006 ; Zhao et al, 2013 ) or systemic LPS-induced ( Song et al, 2013 ) cognitive impairment via inhibition of neuroinflammation. Some COVID-19 patients have been alleviated symptoms using diammonium glycyrrhizinate, an ammonium salt preparation of 18-alpha-GA ( Ding et al, 2020 ; Li et al, 2020 ). This phenomenon could be explained by the anti-inflammatory properties of GA.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C in combination with curcumin and glycyrrhizic acid (VCG plus regime) promoted innate antiviral immunological response and prevented excessive inflammatory response which decreased the risk of inflammation-induced tissue damage [ 88 ]. A non-hospitalised patient with COVID-19 received a traditional Chinese medicine with a steroid-like effect called diammonium glycyrrhizinate in combination with vitamin C [ 89 ]. This regime resulted in significant relieve of the patient’s symptoms.…”
Section: The Beneficial Effect Of Vitamin C In Management Of Covid-19mentioning
confidence: 99%
“…Subsequently, GLR has shown activities against different viruses, including SARS‐associated human and animal coronaviruses, and HIV‐1 13–16 . The increasing scientific interest in GLR and the current COVID‐19 pandemia suggested that GLR may be a potential effective drug against the SARS‐CoV‐2 coronavirus and should be further considered 16–18 . In this study, we summarized serum hepatic enzyme activities in COVID‐19 patients who were treated at Zhongnan Hospital of Wuhan University, evaluated the relationship with the illness severity in COVID‐19 patients, and analyzed the correlation of diammonium glycyrrhizinate (DG, the salt form of glycyrrhizin) treatment and abnormal liver enzyme activities.…”
Section: Introductionmentioning
confidence: 99%